2018
DOI: 10.3168/jds.2017-14200
|View full text |Cite
|
Sign up to set email alerts
|

Variations in methane yield and microbial community profiles in the rumen of dairy cows as they pass through stages of first lactation

Abstract: Considerable interest exists both from an environmental and economic perspective in reducing methane emissions from agriculture. In ruminants, CH is produced by a complex community of microorganisms that is established in early life but can be influenced by external factors such as feed. Although CH emissions were thought to be constant once an animal reached maturity, recent studies have shown that CH yield significantly increases from early to late lactation in dairy cows. The aim of this study was to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
1
19
0
3
Order By: Relevance
“…In this study, we also found that heat stress led to the reduction of acetate-producing Acetobacter . Acetobacter has the ability to produce acetate by oxidizing sugars [35]. During feeding, drinking or rumination, a small amount of oxygen is infused into the rumen fluid, and the taking up of oxygen by Acetobacter helps to construct an anaerobic environment that allows the anaerobic bacteria and archaea to grow better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we also found that heat stress led to the reduction of acetate-producing Acetobacter . Acetobacter has the ability to produce acetate by oxidizing sugars [35]. During feeding, drinking or rumination, a small amount of oxygen is infused into the rumen fluid, and the taking up of oxygen by Acetobacter helps to construct an anaerobic environment that allows the anaerobic bacteria and archaea to grow better.…”
Section: Discussionmentioning
confidence: 99%
“…During feeding, drinking or rumination, a small amount of oxygen is infused into the rumen fluid, and the taking up of oxygen by Acetobacter helps to construct an anaerobic environment that allows the anaerobic bacteria and archaea to grow better. Lyons et al [35] showed a higher relative abundance of Acetobacter in the rumen of cows in the mid-lactation period compared with late-lactation. The reduction in Acetobacter was consistent with the decrease of acetate in the rumen fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rumen harbors a core microbiome (Jami and Mizrahi, 2012; Henderson et al, 2015), in agreement with studies performed in the human gastrointestinal tract (Tap et al, 2009; Qin et al, 2010), the structure, and composition of the rumen microbiome varies within and between animals with differing performance traits. For example, in lactating dairy cattle, the increased methane yield during late lactation in comparison to early lactation within the same individual was found to be associated with significant changes in the ruminal microbial community structure (Lyons et al, 2018); Myer et al (2015) showed different relative abundances of some microbial taxa and operational taxonomic units in animals with different average daily gain (ADG); Shabat et al (2016) focused on residual feed intake (RFI) to demonstrate that highly efficient animals had a less diverse microbiota, being dominated by specific taxa and microbial genes which were involved in simpler metabolic pathway networks when compared to their less efficient counterparts. Other authors have reported that the rumen microbiome varies more between animals than within animals, proposing that the host itself and its physiological parameters have a significant influence on its own rumen microbiome (Li et al, 2009) and, therefore, on the efficiency of feed conversion into energy.…”
Section: Introductionmentioning
confidence: 99%
“…Dit geeft aan dat dierspecifieke eigenschappen, en daarmee samenhangend de samenstelling van de microbiële populatie, het fenotype voor methaanproductie vormen. Individuele verschillen in voeropname en passagesnelheid van voerdeeltjes uit de pens verklaren een groot deel van de methaanproductie tussen dieren (Lyons et al, 2018). Identificatie van hoog en laag emitterende dieren is lastig omdat gedurende de lactatie de emissie intensiteit veranderd (g CH4 per kg FPCM; CH4/kg DS opname of CH4/NEL opname).…”
Section: Erfelijkheid Van Ch4 Emissieunclassified